2005
DOI: 10.1079/asc41640201
|View full text |Cite
|
Sign up to set email alerts
|

Starch digestion site : influence of ruminal and abomasal starch infusion on starch digestion and utilization in dairy cows

Abstract: The effect of site of starch digestion on glucose metabolism in dairy cows was studied. Four multiparous Israeli-Holstein cows in mid lactation were used in a 4 ✕ 4 Latin-square design. Average body weight of cows was 580 ± 38 kg, and average milk yield was 28 ± 3 kg/day. The cows were fitted with ruminal cannula and flexible T-cannulae in abomasum and ileum. Treatments were as follows : CON (control) : water was infused to the rumen. SR (starch-rumen) : 1·5 kg/day of maize starch solution was infused into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A lower voluntary DMI of the observed magnitude with the I treatment was not expected, because previous studies infusing 1,500 g/d of starch led to a 4% decrease of DMI in early lactation (Knowlton et al, 1998) and to an 8 to 9% decrease of DMI in midlactation (Abramson et al, 2005). The decreases in voluntary DMI have been ascribed to the ability of the cows to 1081 GLUCOSE METABOLISM IN PERIPARTURIENT COWS compensate for the additional energy supplied by infusion.…”
Section: Feed Intake and Milk Productionmentioning
confidence: 72%
“…A lower voluntary DMI of the observed magnitude with the I treatment was not expected, because previous studies infusing 1,500 g/d of starch led to a 4% decrease of DMI in early lactation (Knowlton et al, 1998) and to an 8 to 9% decrease of DMI in midlactation (Abramson et al, 2005). The decreases in voluntary DMI have been ascribed to the ability of the cows to 1081 GLUCOSE METABOLISM IN PERIPARTURIENT COWS compensate for the additional energy supplied by infusion.…”
Section: Feed Intake and Milk Productionmentioning
confidence: 72%
“…Larsen and Kristensen (2009) stated that glucose absorption in the small intestine is an efficient source of glucose to the peripheral tissues of dairy cows in early lactation, and at least 67% of the available glucose is recovered in the portal vein without affecting hepatic gluconeogenesis. Abramson et al (2005) concluded that energy efficiency of total nonstructural carbohydrates digested in the small intestine might be greater if they are not digested in the rumen, but rather in the small intestine. Garnsworthy et al (2009) concluded that rumen digestible starch and rumen bypass starch can be equally effective for maintaining plasma insulin and ovarian function by high dairy cows in early lactation.…”
Section: Introductionmentioning
confidence: 99%